Приклад перспективного і екстремального управління захистом в ергатичних системах - Гайдук, І. М. (ХНУРЕ, 2022)
Insurance is offered as a linear approach to the model of financing and the establishment of the local structure protection system. Critical limitations of this model are the type of function in the criteria and the self test, for which the expectation is selected. Thus, the problem of actuarial mathematics to determine the values of insurance premiums when insuring a given financial risk is a good model for describing the financial costs of the design process and long-term protection management. The object of fuser development is mathematical model of transitions between «health-and-state» of a human operator in operatormachine system. The object of study is the state probabilities of human efficiency with the system. The research method is maximization the information entropy.
Keywords: управління захистом